Suplementasi Ampas Teh Fermentasi Dalam Pakan Terhadap Konsumsi Bahan Kering Dan Bahan Organik Pada Puyuh Jantan - Suryowisnu, Bahari; Tugiyanti, Elly; Susanti, Emmy (ANGON: Journal of Animal Science and Technology, 2019)
Background. This study aims was to evaluate the effect of using various forms of tea waste fermented by EM4 on the on dry matter and oraganic matter intake in male quails. Materials and methods. The material used were 100 male quails aged 4 weeks. The experiment was conducted by using in vivoexperiment method and using Completely Randomized Design (CRD) with 4 treatment and 5 repetitions. The treatment were consisted of R0 = quail feed ascontrol feed; R1 = quail feed + fermented tea waste powders as much as 2%; R2 = quail feed + fermented tea waste granules as much as 2%; R3 = quail feed +fermented tea waste leafs as much as 2%. Variables were observed dry matter intake and organic matter intake. Results.The average values of dry matterintake from R0 was 14,60 gram/head/day; R1 was 14,24 gram/head/day; R2 was 14,60 gram/head/day; and R3 was 14,26 gram/head/day (P>0,05). Theaverage values of organic matter intake from R0 was 12,55 gram/head/day; R1 was 12,23 gram/head/day; R2 was 12,54 gram/head/day; and R3 was 12,25gram/head/day (P>0,05). Conclusion. The conclusion of this research was the supplementation of the various forms of tea waste fermented by EM4 on the male quail feed had not increased dry matter intake and organic matter intake yet.